The Transmutations of Arthur Machen: Alchemy in 'The Great God Pan' and The Three Impostors - Poller, Jake (Literature and theology, 2015)
In their biography of Arthur Machen, Reynolds and Charlton note the influence of the alchemist Thomas Vaughan on his work and assert that Helen Vaughan is transformed into first matter in 'The Great God Pan' (1894). The influence of alchemy on Machen's work was eclipsed in the 1990s by the tendency of scholars to map degeneration theory onto Machen's work. In this article, I unpack key alchemical concepts and demonstrate how they relate to the transmutations of Machen's characters. I argue that not only had Machen never heard of degeneration in the pseudo-scientific sense of the word, but also the animosity he displayed towards scientific materialism makes it highly unlikely that he would have knowingly incorporated the concept in his work.